2014
DOI: 10.1590/s0100-736x2014001300006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia do cone medular aplicada à via epidural de administração de fármacos em macacos-prego ( Sapajus libidinosus )

Abstract: RESUMO.-Com este estudo objetivou-se descrever a topografia do cone medular do macaco-prego (Sapajus libidinosus) a fim de fornecer suporte para que a realização de procedimentos anestésicos, bem como exames de mielografia e coleta de líquor, dentre outros procedimentos que utilizam a via epidural. Para tanto foram dissecados oito animais, sendo seis machos e duas fêmeas, de diferentes faixas etárias. Rebateu-se a pele para retirada da musculatura da região dorsal, exposição de toda a coluna vertebral e identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(12 reference statements)
1
6
0
3
Order By: Relevance
“…After the dissection of the dorsal region, from the cranial region to the base of the tail, the spine of A. belzebul was evidenced and showed for all the specimens: 7 cervical vertebrae, 13 thoracic vertebrae, 5 lumbar vertebrae and 3 fused sacral vertebrae (Figure 1). A similar result was found by Silva et al (2013) for Callithrix jacchus and Cordeiro et al (2014) for Sapajus libidinosus. However, Lima et al (2011a) observed a total of 9 lumbar vertebrae for Saimiri sciureus, and Martins et al (2013) observed 7 lumbar vertebrae for Saguinus midas.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…After the dissection of the dorsal region, from the cranial region to the base of the tail, the spine of A. belzebul was evidenced and showed for all the specimens: 7 cervical vertebrae, 13 thoracic vertebrae, 5 lumbar vertebrae and 3 fused sacral vertebrae (Figure 1). A similar result was found by Silva et al (2013) for Callithrix jacchus and Cordeiro et al (2014) for Sapajus libidinosus. However, Lima et al (2011a) observed a total of 9 lumbar vertebrae for Saimiri sciureus, and Martins et al (2013) observed 7 lumbar vertebrae for Saguinus midas.…”
Section: Resultssupporting
confidence: 90%
“…The morphological differences of both the measurement and the topography of the IC, IL, CM and CE among the species described in the literature, show the importance of knowing the location of these structures to apply anesthetics in surgical procedures, which is specific for each species. Silva et al (2013) states that epidural anesthetics should be applied in the lumbosacral region for Callithrix jacchus corroborating the findings of LA for this species, in Saguinus midas it should be applied in the spaces between the vertebral arches of the lumbosacral region (MARTINS et al, 2013), in Sapajus libidinosus, in the epidural space of the lumbosacral region (CORDEIRO et al, 2014) and in Saimiri sciureus in the girdle and pelvic limbs (LIMA et al, 2011a). For A. belzebul, epidural anesthesias should be applied in the lumbosacral region, specifically between L2 and S3 vertebrae.…”
Section: Resultsmentioning
confidence: 73%
“…Em relação ao ratão-do-banhado (Myocastor coypus), uma espé-cie de roedor, também se observou uma semelhança, o qual possui a base do cone em L3-L5 e ápice em L4-L6 [10]. Quanto aos primatas, encontra-se para os macacos-prego, base em L2 e ápice em L5 [4], se assemelhando ao encontrado em Callithrix jacchus.…”
Section: Animalunclassified
“…O valor médio do comprimento do cone medular da espécie Callithrix jacchus (1,4 cm) se apresentou mais próximo ao obtido para o ratão-do-banhado, o qual apresentou um valor médio de 2,0 cm [10], o macaco-prego, no qual foi encontrado valor médio de 2,47 [4], e a preguiça, que apresentou 2,7 cm [7], e significativamente menor do que as médias obtidas para o cachorro-do-mato (10,13 cm) [14], para o cachorro--do-mato-de-orelhas-pequenas (3,9 cm) [15], para o sauim (5,38 cm) [13], para o quati, que apresentou valor de 5,2 a 5,8 cm [5], para o macaco-de-cheiro (3,3 cm) [6], para a paca (3,39 cm) [18], para o javali (Sus serofa serofa), com valor de 3,4 cm [17], para o lobo-marinho (4,4 cm) [9], para o gato mourisco (5 cm) [3], para a ariranha (5,5 cm) [11], para a irara (4,31 cm) [1], para a jaguatirica (8,5 cm) [2], para o guaxinim (5,1 -5,6 cm) [21] e para o lobo-guará (6,5 cm) [8].…”
Section: Animalunclassified
See 1 more Smart Citation